Tibial Plateau Fracture with Ipsilateral Syndesmotic Injury: A Previously Undescribed Maisonneuve-Equivalent Injury Pattern. Issue 1 (January 2020) - Wilson, Jacob M.; Kukoski, Nathan R.; Lunati, Matthew P.; Moore, Thomas
Abstract : Case: A 44-year-old man presented after a motor vehicle crash and was found to have a right tibial plateau fracture and an (initially missed) ipsilateral syndesmotic injury in the setting of a completely intact fibula. He was managed with open reduction and internal fixation of the tibial plateau and syndesmosis. Conclusion: This case represents a novel Maisonneuve-equivalent injury pattern. This diagnosis should be considered in patients with ankle pain in the setting of ipsilateral tibial plateau fracture, and internal fixation of both injuries represents an appropriate treatment option.